ABC of ear, nose, and throat - Bradley, Patrick J. , 1949-; Ludman, Harold (Chichester, West Sussex : Wiley-Blackwell, 2013)
ABC of Ear, Nose and Throat is a long established best-selling guide to the management of common conditions of the Ears, Nose and Throat
Includes bibliographical references and index
Keywords: Otolaryngology; Otorhinolaryngologic Diseases